Effect of particle diameter and injection position on the separation performance of cyclone separators. (March 2016) - Liu, Lin; Dou, Hua-Shu; Chen, Xiaoping
Effects of the particle diameter and particle injection position on the gas–solid two-phase flow have important implications in the tangential inlet cyclone separator. The Navier–Stokes equation coupled with the Reynolds stress model in Euler coordinate system is adopted to describe the gas flow and the discrete phase model in Lagrange coordinate system is used to calculate the particle trajectories. Results show that the separation efficiency varies with the injection position at the inlet cross-section. It is found that the separation efficiency is increased with the increase of the particle diameter. However, when the particle diameter exceeds a critical size, the particles will deposit on the wall of the conical chamber, which leads to lower separation efficiency. The present simulation indicates that the critical size is 24μ m .